1994
DOI: 10.1021/je00015a050
|View full text |Cite
|
Sign up to set email alerts
|

Density and Viscosity of Concentrated Aqueous Solutions of Polyethylene Glycol

Abstract: The densities and viscosities of concentrated aqueous solutions of polyethylene glycol (10-50 mass %) have been measured. The polyethylene glycol samples had average molecular masses of 8000,3350, and 1000. The values of the density from 277 to 298 K show a linear variation with the polyethylene glycol concentration and differ, at most, by 10.07% from those of pure water at the same temperature. In order to estimate the values of dynamic viscosity, an equation is proposed which takes into account the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(175 citation statements)
references
References 6 publications
13
158
3
1
Order By: Relevance
“…Fig. 6 c and d shows, respectively, DTLM and fluorescence microscopy images of the same sample held at T ϭ 75°C for 1 h, a time sufficient to thoroughly disperse nDNA LC domains into the SS nDNA background, especially because highly concentrated PEG solutions typically are less viscous than the nDNA mixtures (13). We found that nDNA domains did not dissolve, so that by cooling again, domains formed in the same locations as they were previously, an occurrence never observed in nDNA mixtures.…”
mentioning
confidence: 99%
“…Fig. 6 c and d shows, respectively, DTLM and fluorescence microscopy images of the same sample held at T ϭ 75°C for 1 h, a time sufficient to thoroughly disperse nDNA LC domains into the SS nDNA background, especially because highly concentrated PEG solutions typically are less viscous than the nDNA mixtures (13). We found that nDNA domains did not dissolve, so that by cooling again, domains formed in the same locations as they were previously, an occurrence never observed in nDNA mixtures.…”
mentioning
confidence: 99%
“…Figure 3b shows air being injected into a mixtureofwater and 10% by weight polyethylene glycol (PEG). PEG is a watersoluble polymer that makes the Newtonian fluidmore viscous, with the viscosity increasing as the PEG concentration increases [50]. Although viscosity was not measured iir this study, Gonzalez-Tello et al [50] indicate the viscosity.…”
Section: X-ray Radiography Imagingmentioning
confidence: 68%
“…Viscosity of PEG increases dramatically with concentration as presented in Ref. 8. A minimal voltage of 6 V at 20 kHz was sent to the piezodispenser and PEG 8000 at 15%, 20%, and 25% concentration was dispensed.…”
Section: -2mentioning
confidence: 99%
“…At a temperature of 298 K, 20% PEG 8000 has a viscosity of 20.2 cp according to Ref. 8, while 30% PEG 8000 has a listed viscosity of 50.9 cp. The maximum viscosity that was dispensed was 30% PEG 8000 at 35 psi with a piezoelectric voltage of 75 V. It was impossible to distinguish separate drops with this high viscosity PEG, and there was significant fluid buildup and dripping from the tip during the starting and stopping of dispensing.…”
Section: -2mentioning
confidence: 99%